Transformation of Education Quality through the Implementation of School-Based Management - Afni Ma'rufah (Global Education Journal, 2026)
This study aims to analyze the application of School-Based Management (SBM) as a strategy to improve the quality of education at SD Ma'arif Ponorogo, a private basic education institution under LP Ma'arif NU that combines general and religious curriculum. Using a qualitative approach with a descriptive design, research data was collected through in-depth interviews, participatory observations, and document analysis, then analyzed through the stages of data condensation, data presentation, and conclusion drawn. The results of the study show that the implementation of SBM at SD Ma'arif Ponorogo runs effectively through participatory planning practices, school autonomy in curriculum and financial management, collaborative leadership of school principals, transparency in fund management, and continuous evaluation. The participation of stakeholders, teachers, parents, school committees, foundations, and the community is a key factor in success, which is evident in their active involvement in program formulation, funding, and implementation of school activities. Nevertheless, schools still face a number of challenges, such as limited infrastructure, technological gaps, the need to improve teacher competencies equally, and differences in perceptions between organizational structures.